"Hot, Black Leather, Whip": The (De)evolution of Female Protagonists in Action Cinema, 1960–2014. (18th April 2016) - Heldman, Caroline; Frankel, Laura Lazarus; Holmes, Jennifer
This article employs a content analysis to investigate whether and how the violent woman archetype in action film changed from 1960 to 2014. We find a trend toward hypersexualized female action leads (FALs), starting in the 2000s. This trend is in line with the broader social trends of hypersexualization during this period, evidenced in a variety of other media sources. We then combine these findings with existing research to discuss the likely affects on viewers' attitudes and beliefs. We suggest that the trend toward hypersexualizing FALs has harmful public health affects and is part of a broader cultural backlash against gender equity.Public Health Significance Statement: This study finds a trend toward hypersexualization of female protagonists in action cinema that contributes to the cultural normalization of female objectification. This normalization has been linked to clinical depression, habitual body monitoring, diet restriction, symptoms of anorexia and bulimia, social physique anxiety, shame about bodily functions, inhibited cognitive functioning, diminished motor skills, diminished sexual pleasure, lower self-esteem, diminished personal efficacy, and lower overall well-being for women.